2005
DOI: 10.1386/etar.1.2.161/1
|View full text |Cite
|
Sign up to set email alerts
|

The Fire Fox: a multi-sensory approach to art education in Lapland

Abstract: This article explores ways in which art education in northern border areas and remote rural districts empowers action. The main emphasis is on an integrated art and science project called the ‘The Fire Fox’ that took place in Finnish Lapland, Utsjoki, in March 2004. The project aims were to extend art into the wider community, develop individual creativity, raise the quality of artistic achievement, strengthen self-esteem and foster shared understanding between people from different cultural backgrounds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…ABAR is especially rooted in process-oriented dialogical and place-specific art forms, such as environmental and community art and community-based art education. Such an approach has been implemented extensively in the field of community-based art education and in multicultural communities in Finnish Lapland (Härkönen, 2018;Hiltunen, 2005Hiltunen, , 2010Hiltunen et al, 2020;Huhmarniemi, 2012;Jokela, 2018).…”
Section: Reformative and Exploratory Teaching In The Arcticmentioning
confidence: 99%
“…ABAR is especially rooted in process-oriented dialogical and place-specific art forms, such as environmental and community art and community-based art education. Such an approach has been implemented extensively in the field of community-based art education and in multicultural communities in Finnish Lapland (Härkönen, 2018;Hiltunen, 2005Hiltunen, , 2010Hiltunen et al, 2020;Huhmarniemi, 2012;Jokela, 2018).…”
Section: Reformative and Exploratory Teaching In The Arcticmentioning
confidence: 99%
“…The Firefox project was an educational art event carried out by several people and organizations in the northernmost municipality of Finland, Utsjoki (Hiltunen, 2005). The project was funded by the European Social Fund and consisted of science and art events with the common theme of the Northern Lights and research into that phenomenon.…”
Section: Case 1: Lapland Snow Art and Designmentioning
confidence: 99%
“…In local schools, they are instruments for integrating school subjects and for the eventuality that culminates in thematic work. The project has made visible and celebrated the strengths of the unique multicultural community and the splendid local nature (Hiltunen, 2005(Hiltunen, , 2008.…”
Section: Case 1: Lapland Snow Art and Designmentioning
confidence: 99%
“…Ruilun (2005) showed the influences from Chinese culture in art education in elementary and secondary schools. Hiltunen (2005) discussed the educational significance of a project that was related to the northern culture of Finland. Moreover, Chang (2010) indicated that she found ways of expanding students' cultural understanding, powers of observation, and critical thinking and problem-solving skills through utilising Taiwanese culture in art education.…”
Section: Introductionmentioning
confidence: 99%